▼Grazax for hay fever – what's new?. Issue 5 (6th May 2010) - Unknown
Abstract : In 2008, we reviewed Grazax, a sublingual tablet containing standardised allergen extract of grass pollen.1 At the time, this product was licensed for the treatment of adults with proven grass-pollen-induced rhinitis and conjunctivitis (hay fever). However, we were not convinced that the effect on rhinoconjunctivitis symptom scores in published trials was clinically relevant. Also, given that no published studies had compared Grazax with symptomatic therapies or subcutaneous immunotherapy for hay fever, it was expensive and its long-term efficacy and safety were not known, we could not recommend its use.1 Since our review, the terms of the marketing authorisation for Grazax have been changed, such that it is now described in the summary of product characteristics (SPC) as a "disease-modifying treatment", and the drug is now also licensed for use in children aged 5 years and above.2 Here we assess the latest evidence for Grazax and reconsider the drug's place in the management of patients with hay fever.